Spectroscopic and structural properties of 1 mol% Tb3+ doped 2B2O3 + 5ZnO + 30PbO + 62P2O5 glass for green laser application. Issue 5 (1st April 2020) - Sharma, Subhash; Jana, Samar; Mitra, Subrata
Abstract: A detailed study on optical as well as structural properties of 1 mol % Tb 3+ ions doped 2% B2 O3 + 5% ZnO +30% PbO +62% P2 O5 glass has been reported in this paper. In order to explore the structural properties of the glass we have studied XRD, FTIR and Raman spectra. The spectroscopic characteristics have been investigated by analysing the absorption spectra, photoluminescence spectra, fluorescence decay profile and CIE color chromaticity. The optical band gaps are also estimated. The absorptions are obtained in the UV–Visible–NIR region and among them the most prominent peak is found at around 376 nm related to 7 F6 → ( 5 D3, 5 G6 ) transition. The excitation spectra also exhibits that the potentially strong and intense excitation occurs at 376 nm, corresponding to ( 5 D3, 5 G6 ) multiplets, and hence to perform the photoluminescence measurements this energy has been utilized as excitation energy. The emission spectra, recorded at room temperature indicate eleven emissions, including a comparatively strong and intense peak at 541 nm which emits strong green color as a consequence of 5 D4 → 7 F5 transition. By the proper fitting of the luminescence decay profile, we have obtained the experimental lifetime of the excited states. The radiative parameters are also calculated by evaluating the best set of Judd-Ofelt parameters. The CIE color chromaticity shows the high color purity of 71.8%. Our investigation reveals that the glass sample produces higher quantum efficiency of 80% and it is suitable for application as a strong green color emitting laser material.